2017
DOI: 10.3390/ijerph14111287
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Pediatric Motor Vehicle Crashes on U.S. Native American Indian Lands Compared to Adjacent Non-Indian Lands: Restraint Use and Injury by Driver, Vehicle, Roadway and Crash Characteristics

Abstract: There are large disparities in American Indian pediatric motor vehicle (MV) mortality with reports that several factors may contribute. The Fatality Analysis Reporting System for 2000–2014 was used to examine restraint use for occupants aged 0–19 years involved in fatal MV crashes on Indian lands (n = 1667) and non-Indian lands in adjacent states (n = 126,080). SAS GLIMMIX logistic regression with random effects was used to generate odds ratios (OR) with 95% confidence intervals (CI). Restraint use increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…While the majority of children were restrained in a child restraint system, about one-fifth of children were unrestrained or restrained in a non-child restraint system. The finding that unrestrained children involved in a fatal crash were more likely to be transported by drivers who were unrestrained, younger (aged < 20 years) and positive for alcohol is consistent with previous studies (Hertz, 1996; Huang et al, 2016; Oh et al, 2017). These findings of lack of restraint use by drivers suggests an area where enforcement of seat belt laws in adults transporting children might improve the safety of child passengers as well.…”
Section: Discussionsupporting
confidence: 91%
“…While the majority of children were restrained in a child restraint system, about one-fifth of children were unrestrained or restrained in a non-child restraint system. The finding that unrestrained children involved in a fatal crash were more likely to be transported by drivers who were unrestrained, younger (aged < 20 years) and positive for alcohol is consistent with previous studies (Hertz, 1996; Huang et al, 2016; Oh et al, 2017). These findings of lack of restraint use by drivers suggests an area where enforcement of seat belt laws in adults transporting children might improve the safety of child passengers as well.…”
Section: Discussionsupporting
confidence: 91%
“…In an analysis of fatality data from 2000 to 2014, Shin and colleagues found that restraint use in Indian lands was significantly lower than that of non-Indian lands. 29 Building upon early observational reports, 33,34 our findings also suggest that fatally injured black children also face a higher risk of unrestraint and inappropriate restraint than white children. Furthermore, the observed racial difference in age-appropriate CRS use remained statistically significant, even after we adjusted for relevant risk factors.…”
Section: Discussionsupporting
confidence: 61%
“…3,5,19 Furthermore, observational studies have connected several factors with the misuse or nonuse of CRSs, including legislation, socioeconomic indicators, race, age (of the child and parent), ease of the CRS installation, and parental beliefs. 4,20-29 Although previous studies have shed light on the circumstances related to restraint use, few have analyzed population-level MVC fatality data using the AAP’s definition of age-appropriate CRS use, while simultaneously adjusting for multiple risk factors. The objectives of this study were to identify factors associated with age-appropriate CRS use in fatal MVCs, as well as characterize overall patterns in CRS use among fatally injured 4- to 7-year-old child passengers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, New York's observed front seat belt wearing was at 93% [29]. However, seat belt wearing is lower in fatal crashes, in nighttime crashes, in teens not covered by graduated driver licenses, in rear seated occupants, in taxis and vehicles for hire, in older vehicles, in those using alcohol or drugs and across geographical areas [1,[30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%